Melt‐synthesis of LiFePO4 over a metallic bath. (4th February 2019) - Villazon, Hernando; Sauriol, Pierre; Rousselot, Steeve; Talebi‐Esfandarani, Majid; Bibienne, Thomas; Gauthier, Michel; Liang, Guoxian; Dollé, Mickaël; Chartrand, Patrice
Abstract: Compared with large‐scale processes, the LiFePO4 (LFP) melt‐synthesis is a low‐cost method with short dwell times and rapid reaction rates. However, secondary phases and impurities remaining in the olivine structure lower the cathode's electrochemical properties. Starting from a low‐cost Fe 3+ precursor, we evaluated tin and silver charged metallic baths to purify the melt‐synthesis of LiFePO4 at laboratory scale. In the tin bath exploration, an x‐ray diffraction (XRD) confirmed the olivine structure and a temperature‐dependent generation of Li3 PO4 and Li4 P2 O7 . An SEM image analysis identified tin‐rich phases (Sn x P y O z ) segregated from the LFP structure and Fe x P phases on the internal walls of the crucible. A multi‐element analysis (ICP‐AES) detected more than 0.03 g of Sn/g of LFP. The tin bath prepared samples delivered up to156 mAh/g of LFP in a carbon‐free basis, 3 % lower than the capacity of the high purity Fe2 O3 ‐based material at 0.1 C. The silver bath‐based LFP samples produced cleaner XRD patterns (less than 160 ppm of Ag in the LFP ingots), closer to the estimated molar ratios and neither silver compounds nor silver oxides. In this case, the sample delivered 161 mAh/g of LFP, the same capacity as the cathode prepared without a metallic bath. Starting from a commodity Fe 3+ source, future work should explore the silver bath roles as a reactive media, a heating source, a crucible insulator, and a potential contaminant trap for the melt‐synthesis of LiFePO4 .